SOROCONVERSÃO APÓS VACINA CONTRA HEPATITE B EM PESSOAS VIVENDO COM HIV - NETO, João Borges de Oliveira; CURY, Eunice Stella Jardim; MENIN, Iris Bucker Froes; UEHARA, Silvia Naomi de Oliveira (ANAIS DO ENIC, 2023)
-